Spinal Cord Injury Management through the Combination of Stem Cells and Implantable 3D Bioprinted Platforms - Atefeh Zarepour (MDPI AG, 2021)
Spinal cord injury (SCI) has a major impact on affected patients due to its pathological consequences and absence of capacity for self-repair. Currently available therapies are unable to restore lost neural functions. Thus, there is a pressing need to develop novel treatments that will promote functional repair after SCI. Several experimental approaches have been explored to tackle SCI, including the combination of stem cells and 3D bioprinting. Implanted multipotent stem cells with self-renewing capacity and the ability to differentiate to a diversity of cell types are promising candidates for replacing dead cells in injured sites and restoring disrupted neural circuits. However, implanted stem cells need protection from the inflammatory agents in the injured area and support to guide them to appropriate differentiation. Not only are 3D bioprinted scaffolds able to protect stem cells, but they can also promote their differentiation and functional integration at the site of injury. In this review, we showcase some recent advances in the use of stem cells for the treatment of SCI, different types of 3D bioprinting methods, and the combined application of stem cells and 3D bioprinting technique for effective repair of SCI.